The interaction of dispersal and control methods for the riverine tsetse fly Glossinapalpalisgambiensis (Diptera: Glossinidae): a modelling study. Issue 1 (19th September 2012) - Barclay, Hugh J.; Vreysen, Marc J. B.
Abstract: We used a spatial model of a riverine tsetse fly species Glossina palpalis gambiensis life cycle to investigate the interaction between their dispersal and three control methods and to document these interactions using sensitivity analyses. The model is currently limited to gallery forest habitat inhabited by Glossina palpalis gambiensis in the dry season in the sub‐humid zone of West Africa. The control methods modelled were traps and targets (TT), insecticide‐treated livestock (ITL), and the sterile insect technique (SIT). Both distance dispersed (up to 800 m) and percent of flies dispersing each day (up to 60 %) increased the efficiency of control by TT. Most of this increase occurred for low values of both distance dispersed and percent dispersing, but the increase continued up to the limits tried. The daily movement of cattle assisted the control program and when movement was considerable (up to 600 m daily) the effects were greater than the effects of tsetse dispersal. Random dispersal decreased aggregation and equilibrium population size, and thus also increased the efficiency of SIT. Dispersal that was mostly oriented towards clumps was of much less value for SIT but acted on TT and ITL similarly to random dispersal.